Evaluate the correlation of Inflammatory Cytokines with Chlamydia pneumonia in Coronary Atherosclerotic Patients - AL-Barzinji, Ruqaya M.; Rahman, Lajan Q. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Coronary atherosclerosis is an inflammatory disease, caused by high concentrations of plasma cholesterol, in particular those with high concentrations of low-density lipoprotein cholesterol, which considered as one of the principal risk factors for atherosclerosis. Objective: The study focused on detecting risk factors and biomarkers for coronary atherosclerotic in order to develop interventions preventing their progressions. Patients and Methods: The present case control study was carried out between December 2012 and May 2013, in Hawler cardiac center, 74 coronary atherosclerotic patients were enrolled in our study (44 males and 30 females), their age ranged between 30 years to 75 years old, 25 (33.8%) were type 2 diabetes, 51 (68.9%) were hypertensive and 29(39.2%) were obese. Apparently 40 healthy individuals were also joined in this study. The sera were subjected to assessment of some inflammatory biomarkers including high sensitive C- reactive proten (CRP), Interleukin-6(IL-6), Tumor Necrosis Factor-alpha (TNF-α), IL-10, leptin, leptin receptor and Chlamydia pneumonia (C.pneumonia). Results: Serum concentrations of high sensitive CRP, TNF-α, C.pneumonia and IL-10 in obese coronary atherosclerotic patients (CAPS) were significantly higher than non-obese patients (P≤0.01), indeed IL-6, leptin and leptin receptor also significantly increased in obese patients(P≤0.05). Same results with serum CRP, IL-6 and IL-10 levels in diabetic patients than non-diabetic patients (P≤0.05). However, TNF-α in diabetic patients was significantly higher than non-diabetic patients (P≤0.01). Serum concentration of high sensitivity CRP in hypertensive patients was statistically significant than non-hypertensive patients (P≤0.05). Conclusions: Our study revealed that various factors have been introduced in the pathophysiology of atherosclerosis such as: age, sex, diabetes, hypertension, obesity, defect in lipid metabolism and change in the concentration of various lipoproteins of cholesterol.